Antidepressant Game, Smartphone QoE, and Rescue Robots - Haniff, David; Chihani, Bachir; Bertin, Emmanuel; Crespi, Noël; Kececi, Emin Faruk (Institute of Electrical and Electronics Engineers (IEEE), 2012)
This issue's Works-In-Progress features three diverse entries. The first entry, "Online Game for Battling Depression," by David Haniff, is an online game designed to help individuals understand situations that can trigger depression, while the second entry ("Android-Based QoE Management Framework," by Bachir Chihani, Emmanuel Bertin, and Noel Crespi) presents a smartphone framework for measuring users' quality of service and experience in different mobile contexts while they use multimedia services. The final entry, "Rescue Robts: Supporting Adaptive Navigation," by Emin Faruk Kececi, discusses the benefits of using existing commercial electronics to implement dynamic skid control in a search-and-rescue robot.